Peculiarities of functioning confixal nouns in O. Dovzhenko’s literary works (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article gives a broad outline of confixal nouns in a fictional text, their semantic, world building and functional peculiarities basing on Dovzhenko’s cinematic stories. It also analyses derivations built by joining such confixes with postpositive components as -/й/а,-ок, -ник, -иц(я), ø (the second part is not materially expressed) as well as various  prepositive elements to the   motivational basis.
Keywords: confix; postpositive component; confixal derivative